Draft Annual Plan (1968-69) Part-I (Notes) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1968)
The Fourth Five Year Plan of the Union Territory of Pondicherry envisages an outlay of Rs.12.25 crores. An expenditure of Rs. 142.071 lakhs (net) (Rs. 151.53 lakhs - Gross) was incurred during 1966-67 as against a annual plan outlay of Rs. 214.02 lakhs, and a budget outlay of Rs. 200.54 lakhs.
Union Territory of Pondicherry